La déséthicisation de la liberté d’expression - Gilles Gauthier (Communication)
The notion of ethicization often refers to a process in which an ethical concern is integrated into a different type of analysis or body of doctrine. In this article, the author considers the idea of de-ethicizing freedom of expression and how that would affect the analysis of public debate. First, the author explains what de-ethicization is and how we perceive freedom of expression as a result. He goes on to analyze some implications of the de-ethicization of freedom of expression on the analysis of public debate where de-ethicization is an issue or where de-ethicization is the topic being debated. Last, he looks at the extent to which the de-ethicization of freedom of expression affects how it is framed from an ethical perspective and how best to understand the moral judgments posited on the notion.